(untitled) - McEwen, P. K. (New York, 2001)
Lacewings are predatory insects which attack and kill large numbers of insect pests. Lacewings in the Crop Environment addresses both the theoretical and practical aspects of lacewing biology and their use in crop protection. The book opens with a section on lacewing systematics and ecology. Next, lacewings as predators in a wide variety of commercially important crops are reviewed and this is followed by a section on the principles of using lacewings in pest control. The possible impact of genetically modified crops on lacewing populations is also discussed. Finally, a fascinating array of case studies of lacewing use in many crops from around the world is presented, and future uses of lacewings speculated upon. Lacewings in the Crop Environment is an essential reference work and practical handbook for students, researchers of biological control, integrated pest management and agricultural science, and for field workers using lacewings in pest management programmes worldwide.
Keywords: Lacewings,Agricultural pests; Biological control